Remote and Hybrid Work and Sedentary Behaviour Among Working Adults: A Scoping Review of Behavioural Evidence and Cardiometabolic Research Gaps - siying qiu; hanyu du; Yuexian Tao (Journal of Public Health and Preventive Medicine, 2026)
Background: Remote and hybrid work arrangements may improve autonomy and reduce commuting, but may also reduce routine movement and promote prolonged sitting. Evidence on sedentary behavior in these settings has expanded, whereas direct evidence on cardiometabolic outcomes remains limited. Objective: To map behavioral evidence on sedentary exposure in remote and hybrid work, describe its measurement and distribution across work arrangements, and characterize cardiometabolic outcomes as an evidence gap. Methods: We conducted a scoping review in accordance with the JBI methodology and reported it following the PRISMA-ScR guideline. PubMed, Embase, Web of Science Core Collection, PsycINFO, CINAHL, and Scopus were searched from database inception to 19 July 2026, supplemented by backward and forward citation searching. Two reviewers independently screened titles and abstracts and assessed potentially eligible full-text reports. Inter-reviewer agreement was high (Cohen's κ=0.82). Data were charted using a standardized form and independently verified by a second reviewer. Methodological appraisal was completed using the latest revised design-specific JBI critical appraisal tools. Results: The searches identified 360 records. After removal of 34 duplicates, 326 records underwent title-and-abstract screening, and 161 reports proceeded to full-text assessment. Following exclusion of 127 full-text reports, 34 reports representing 30 unique studies were included. Thirty-three reports representing 29 unique studies contributed quantitative or intervention evidence, and one intervention-development report contributed contextual evidence. Most studies reported greater occupational or total sitting, longer sedentary bouts, or fewer steps on home-working days, although several device-based studies reported null or mixed findings. Direct cardiometabolic evidence remained sparse and consisted mainly of one small cross-sectional study and short-term intervention trials without clear cardiometabolic improvement. Conclusions: Remote and hybrid work are often associated with greater sedentary exposure, particularly during working hours, but estimates vary across work arrangements and measurement methods. Direct evidence on long-term cardiometabolic outcomes is insufficient and largely cross-sectional. Movement-break, workstation, and organizational strategies may be considered to reduce occupational sitting, but their longer-term health effects warrant evaluation.